Development of HOTS-Based Arabic Exam Questions According to Bloom’s Taxonomy for Fifth Grade Students at Darul Hikmah Islamic School Tangerang - Syifa Amalia Nurkhalifah Fitrian; Siti Uriana Rahmawati; Raswan (Naatiq: Journal of Arabic Education, 2025)
This study aims to develop Higher Order Thinking Skills (HOTS)-based exam questions for Arabic language subjects in the fifth grade at Darul Hikmah Integrated Islamic School, Tangerang City, grounded in Bloom’s Taxonomy framework. The background of this research stems from the need to improve the quality of Arabic language assessments, which have traditionally focused on memorization and basic understanding, by incorporating instruments that evaluate students' higher-order thinking abilities. There is a lack of empirically validated HOTS-based questions, particularly in Islamic elementary schools. The study employed the 4D development model (Define, Design, Develop, and Disseminate) and involved a sample of 20 fifth-grade students. The results of the study showed that: (1) the instrument was theoretically highly valid, receiving a validation score of 91.5% from two expert reviewers; (2) questions number 1, 2, 4, 5, and 9 were empirically valid, with point-biserial correlation values exceeding 0.468; (3) the instrument’s reliability was categorized as moderate, with a KR-20 value of 0.59; and (4) the average difficulty index was 0.52, indicating good question quality. Therefore, the developed HOTS-based questions are feasible to be used as effective assessment tools to measure higher-order thinking skills in Arabic language learning at the elementary school level.